Phenotyping of spring bread wheat cultivars from Kazakhstan based on grain quality traits (Experimental biology, 2016)
Kazakhstan is ninth largest country in the World by territory and one of the leading exporter of wheat on the World market. Therefore a stable improvement of high quality grain productivity, including wheat, which is a major strategic commodity, is one of the main directions for food security both with in the country and in the World.  The collection of bread wheat Triticum aestivum L. consisting from 96 cultivars and promising lines, including those that officially registered in the Republic of Kazakhstan, were analyzed by a number of grain quality traits. The list of traits included grain hardness, protein and gluten content, high and low molecular subunits of glutenin, quantity and quality of gluten, plumpness, glassiness, sedimentation, starch content, and falling number. The description of each studied trait, assessment and interpretation of grain quality in wheat breeding, methods and protocols for grain quality tests and their products in state and international competitive trials were provided. Studied panel of accessions grown in wet conditions was characterized as strong wheat according to their protein content, high valuable group according to their glassiness and sedimentation, and as unstable group of wheat according to gluten quality. Obtained results confirm wide range of grain quality traits in the collection of wheat from Kazakhstan that tested in multiple years in Kostanai region (Karabalyk breeding station). The information will be used for the genome wide association mapping study of grain quality of wheat.
Keywords: spring bread wheat; grain quality; grain hardness; protein content; gliadin; glutenin; gluten; sedimentation.